PROGRAM BUDIDAYA MADU TRIGONA DIKAMPUNG GARDU TANJAK PANDEGLANG, KOLABORASI DENGAN HIMPUNAN PETERNAK LEBAH CLANCENG (HIPEC) DAN LPPM UNIS TANGERANG DAN MASYARAKAT, DARI PERSPEKTIF EKONOMI DAN HUKUM: budidaya, ekonomi, hukum - Lesmana, Sri Jaya; Lestari, Tiara Ayu; ., Ahmad (Servecivitatis, 2022)
Abstract The village of Gardu Tanjak is located in Pandeglang Village, Pandeglang District, Pandeglang Regency, Banten Province. This Tanjak Gardu Village is one of the areas where Trigona honey is cultivated. Cultivation of Clanceng/Teuweul honey, honey from teuwel bees or stingless bees can be bred in the area. The type of bee that is cultivated is the Apis Trigona species with the Trigona Leaviceps species. Beekeeping produces honey, bee pollen, and propolis, which are very beneficial for health. Economic growth in Indonesia is also influenced by education which will produce more professional qualities of Human Resources (HR) both for the industrial sector, and from there it will have an impact and influence. The case described in the illustration provides evidence that when the laws and regulations are inconsistent and overlapping, it is a business (port) but requires support from various parties, especially in the legal field. Development in the economic field cannot run alone, but requires support from various parties, especially in the legal field. Law has a very central role in the success of a country’s economic development, especially in providing business and investment certainty. The case presented in the illustration provides evidence that when laws and regulations are inconsistent and overlapping, a business (port) will not achieve the expected level of performance, and in turn even hinder the development of other sectors.